MEKANISME BONDING DAN NILAI PERUSAHAAN - M. Budi Widiyo Iryanto; Sugeng Wahyudi (University of Merdeka Malang, 2010)
This study aimed to analyze the role of agency costs mediating the relationship between the mechanism ofbonding and the company values, and analyze the role of the corporate environment moderating therelationship between the mechanism of bonding and the value of the company. Industrial sector nonfinancialcompanies listed on the Indonesia Stock Exchange as an object of research for the period 2006-2008. Based on purposive sampling method, it obtained samples of 46 companies or 138 units of analysis.Completion estimated path model approach Partial Least Square (PLS) through Smart PLS software version2.0 M3. The findings of this study are the remuneration as a bonding mechanism had a significant positiveeffect on firm value. Equity agency costs mediated the influence of bonding mechanisms of corporate value,while the agency costs of debt did not mediate the effect of bonding mechanism to value the company. Itmoderated the relationship between corporate environmental and bonding mechanism to value the company.Finally, the study found evidence of practices of public companies control agency problem in Indonesiasupported the integration of contingency theory and agency theory.